2023
DOI: 10.1007/s11033-023-08711-y
|View full text |Cite
|
Sign up to set email alerts
|

MiR-138-5p improves the chemosensitivity of MDA-MB-231 breast cancer cell line to paclitaxel

Mina Rasoolnezhad,
Reza Safaralizadeh,
Mohammad Ali Hosseinpour Feizi
et al.

Abstract: BackgroundChemotherapy is a predominant strategy for breast cancer (BC) treatment and paclitaxel (PTX) has been known as a conventional chemotherapeutic drug. However, insensitivity of BC cells to PTX limits the antitumor effects of this agent. MicroRNAs are closely related to BC which are suggested as therapeutic factors in the combination therapy of BC. We examined the possible e cacy of miR-138-5p restoration in combination with PTX to impove BC treatment. Methods and ResultsThe human breast cancer cell lin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Indeed, the misregulation in cell cycle related siganling pathways results in the unlimited proliferation of tumour cells. Moreover, it was reported that one of the approaches for increasing the sensitivity of cancer cells to chemotherapeutics was to in synergy them with cell cycle regulators [24]. Preclinical studies have shown that Propofol can significantly inhibit the development of breast cancer tumors[29; 31; 36].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the misregulation in cell cycle related siganling pathways results in the unlimited proliferation of tumour cells. Moreover, it was reported that one of the approaches for increasing the sensitivity of cancer cells to chemotherapeutics was to in synergy them with cell cycle regulators [24]. Preclinical studies have shown that Propofol can significantly inhibit the development of breast cancer tumors[29; 31; 36].…”
Section: Discussionmentioning
confidence: 99%